MENJADI SMART DIGITAL DESA WISATA CIBIRU WETAN BERKAT PENDAMPINGAN DAN PELATIHAN - Gunawan, Syam; Herlinawati, Erna; Wijaya, Dina Yulia; Setiawati, Liya; Surjaatmadja, Surachman; Nurhasanah, Neneng (Jurnal Abdimas Bina Bangsa, 2025)
Through the Regent's Decree no. 556/KEP.770- DISBUDPAR/2020 concerning the Designation of Tourist Villages in the Bandung Regency Area, there is a lot of potential in the Cibiru Wetan Tourism Village area, including having beautiful natural phenomena, which can be an attraction for tourists to visit the Cibiru Wetan Tourism Village. and become the tourist destination of choice for domestic and foreign tourists to relieve fatigue and calm the mind (refreshing), by enjoying the beauty of the city of Bandung, regional tourism education in the form of traditional arts diverse and learn from nature and local culinary specialties. The aim of carrying out activities is to increase the independence of partners in digitizing the promotion of the Cibiru Wetan Tourism Village, Cileunyi District, Bandung Regency through the "Smart Digital" program so that it is widely known by domestic and foreign tourists, which has an impact on increasing the number of tourist visits. The method used is qualitative with the aim of finding out what is currently happening. The data analysis used in this service is an interactive model which has four stages, namely data collection, data reduction, data display, and conclusion/verification. Interactive model analysis was carried out during data collection and after completing data collection on answers to interviews.